Advances in spinal stabilization - Haid, Regis W.; Subach, Brian R.; Rodts, Gerald E (Progress in neurological surgery, 2003)
Dramatic changes in spinal stabilization have taken place in the last years and the pace of change continues to accelerate. This volume is an excellent mirror of the evolution of spinal stabilization. It brings together the latest and most comprehensive reviews in minimally-invasive and novel surgical approaches and spinal stabilization techniques. Highlights in new biomaterials including radiolucent, bioresorbable, and standard titanium are discussed by experts. Biological advances including the use of bone morphogenetic protein in anterior lumbar interbody fusion as well as computer-assisted image-guided surgical techniques are demonstrated. The section on instrumentation and technique represents the most up-to-date advances in surgical technique and management of spinal disorders. Illustrations included in each chapter document these excellent papers.Because it is a must for all surgeons performing spinal surgery to keep up-to-date in this fast moving field this book is indispensable reading for them. Neurosurgeons and orthopedic surgeons will find a wealth of information in this volume on the developments in surgical approaches, biomaterials and implants, and biological innovations